2020
DOI: 10.1108/gm-09-2019-0154
|View full text |Cite
|
Sign up to set email alerts
|

Opt-out stories: women’s decisions to leave corporate leadership

Abstract: Purpose The purpose of this paper is to explore how the challenges to women’s authentic leadership identities contribute to their decisions to abandon leadership positions mid-career. It examines the critical career moments and underlying themes behind these women’s decisions to leave. Design/methodology/approach This paper is based on semi-structured interviews (n = 9) with women between the ages of 32-53 who had opted-out of mid-level corporate leadership positions. Findings The study found that work–lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
(102 reference statements)
0
6
0
1
Order By: Relevance
“…As reviewed earlier, emotional labor is costly both psychologically ( Richards and Gross, 2000 ; Brotheridge and Grandey, 2002 ; Beal et al, 2006 ; Hopp et al, 2010 ; Scott and Barnes, 2011 ) and physically ( Grandey, 2000 ; Johnson and Spector, 2007 ; Hopp et al, 2010 ), and has a negative impact on work-related outcomes such as performance and job satisfaction ( Judge et al, 2009 ; Cheung and Tang, 2010 ; Hülsheger and Schewe, 2011 ). Qualitative studies have revealed that the difficult task of expressing one’s authentic self while acquiescing to external expectations to perform emotional labor may drive women to opt out of leadership positions ( Frkal and Criscione-Naylor, 2020 ). Additional research is needed to provide quantitative data to support these findings and to further examine the mechanisms through which emotional labor demands push women out of high-power roles, promoting gender segregation at the top of organizations.…”
Section: Implications For Gender Equality At the Top Of The Hierarchymentioning
confidence: 99%
“…As reviewed earlier, emotional labor is costly both psychologically ( Richards and Gross, 2000 ; Brotheridge and Grandey, 2002 ; Beal et al, 2006 ; Hopp et al, 2010 ; Scott and Barnes, 2011 ) and physically ( Grandey, 2000 ; Johnson and Spector, 2007 ; Hopp et al, 2010 ), and has a negative impact on work-related outcomes such as performance and job satisfaction ( Judge et al, 2009 ; Cheung and Tang, 2010 ; Hülsheger and Schewe, 2011 ). Qualitative studies have revealed that the difficult task of expressing one’s authentic self while acquiescing to external expectations to perform emotional labor may drive women to opt out of leadership positions ( Frkal and Criscione-Naylor, 2020 ). Additional research is needed to provide quantitative data to support these findings and to further examine the mechanisms through which emotional labor demands push women out of high-power roles, promoting gender segregation at the top of organizations.…”
Section: Implications For Gender Equality At the Top Of The Hierarchymentioning
confidence: 99%
“…Other scholars have drawn attention to structural issues, such as inflexible jobs, low opportunity for advancement, and discrimination in the workplace, that push women out of the workforce (Barbulescu and Bidwell, 2013;Lim and Mohd Rasdi, 2019;Mainiero and Sullivan, 2006;Th ebaud, 2015). Studies have also highlighted that cultural expectations to conform to traditional gender roles may account for women's decisions to opt-out of corporations (Frkal and Criscione-Naylor, 2020). However, we know little about women who leave corporate positions to become entrepreneurs, and even less about those who stay on the entrepreneurship path (Heilman and Chen, 2003;Sullivan et al, 2007;Terjesen, 2005;Wheadon and Duval-Couetil, 2019).…”
Section: 5mentioning
confidence: 99%
“…While there is a significant body of research examining women's careers, the phenomenon of entering and staying in entrepreneurship is relatively under-explored. Considerable research has been conducted to highlight women's career decisions to opt-out of corporate positions (Frkal and Criscione-Naylor, 2020;Mainiero and Sullivan, 2005), but little is said about those who leave to become entrepreneurs (Mainiero and Sullivan, 2006;Terjesen, 2005;Wheadon and Duval-Couetil, 2019). Many of the existing efforts that examine women entrepreneurs have been devoted to documenting differences between men and women entrepreneurscparticularly the obstacles faced by women business owners (Castellaneta et al, 2020;Jennings and Brush, 2013;Gupta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Í rannsókninni sem þessi grein byggir á er miðað við einstaklinga sem höfðu sinnt leiðandi hlutverkum í atvinnulífinu og gegnt framkvaemdastjórastöðu eða sambaerilegu í stórfyrirtaekjum eða stofnunum. Ýmsar vísbendingar eru um að konur í aeðstu stjórnunarstöðum kjósi að fara úr þeim á miðjum aldri (Frkal og Criscione-Naylor, 2020;Zimmerman og Clark, 2016). Til þess að kanna þetta á Íslandi var sjónum beint að konum í aeðstu stjórnunarstöðum, sem um eða eftir miðjan aldur kusu að gera róttaekar breytingar á starfsferli sínum, þrátt fyrir að hann hafi verið farsaell og árangursríkur.…”
Section: Turning Point What Drives Female Leaders To Opt Out Of Top Executive Positions During Middle Age 1 Inngangurunclassified